Phenomenological Exploration in Mathematics Education - Rotua Simbolon; Lukman El Hakim; Tian Abdul Aziz (Study Program of Mathematics Education of Unimed Postgraduate Program, 2023)
We don't know what will happen tomorrow. Yesterday is a memory, today is a reality and tomorrow is a hope. Who would have thought that the corona virus would become one of the elements forming a new life cycle not only for Indonesia but for the whole world. During the Covid-19 pandemic, Large-Scale Social Restrictions (PSBB) were implemented, this had an impact on the implementation of face-to-face (online) learning. Educational institutions must also change direction. Work from home. Going online is one way to stay afloat. Learners at all levels, learn online. Some are still not familiar with this method, especially those in regions or villages, so that in its implementation there are obstacles that result in the implementation of the learning process not being optimal. Those who live in cities experience different obstacles again. Learning that should be carried out face-to-face has changed to online. One of the differences that exist is seen from progress, namely those who live in cities and in villages have different difficulties. Not to mention the other variants. This article aims to find out the obstacles experienced by students during the implementation of online learning in Mathematics lessons. The approach used is a phenomenological approach. How does the exploration of phenomenology play a role in the mathematical approach. The hope is that with this approach you can get information regarding the implementation of the online learning process for learning Mathematics during the Covid-19 pandemic. Exploration of Mathematics Education is seen from a phenomenological attitude, which means that it starts with entering phenomena through practice. The exercises provided are designed so that participants are able to illustrate, mention, give directions and are able to associate meanings and differences. Actually someone gets something in learning more than one's intentions, it doesn't even matter whether a teacher teaches well. For this reason, a creative teaching method is needed in learning mathematics so that there is good interaction between students and teachers. Conclusion: The process of learning mathematics online was not optimal during the pandemic due to several factors that affected the smooth implementation of learning.